FAST PYROLYSIS OF RUBBER WOOD SAWDUST FOR BIO-ENERGY AND BIO-CHEMICAL - MAZLAN, MOHAMMAD AMIR FIRDAUS (2016)
Biomass is a renewable resource and has abundant amount. Ordinarily, biomass waste has no or little economic values and often causes disposal problems. One of the major wastes from plantation and forestry industries is rubber wood remains. The prospect of energy generation and chemical derivation based on biomass utilization is drawing great attention. One of the promising technologies to generate valuable fuels and chemical products from biomass is through a fast pyrolysis process. It is a heating process of organic materials at a medium temperature between 400 to 600 °C under the absence of oxygen and in a short retention time of a few seconds for vapor product. It converts biomass into liquid (bio-oil), solid (bio-char), and gas (pyrolysis gas) products. In this research, rubber wood sawdust (RWS) residue with a size range of 0.15 to 0.50 mm was pyrolyzed in two types of pyrolyzer, drop-type fixed bed and bubbling fluidized bed pyrolyzers.